Simultaneous implementation of enhanced resolution and large dynamic range for fiber temperature sensing based on different optical transmission mechanisms - Ni, Wenjun (2019)
In this paper, a high resolution and large dynamic range fiber optic temperature sensor without measurement crosstalk has been proposed. Two combinational mechanisms of anti-resonant reflecting optical waveguide and inline Mach-Zehnder interference structure are integrated in single hole twin eccentric cores fiber. The dual-effect composite spectrum is consist of several dominant resonant wavelengths and comb pattern, which are corresponding to the two above-mentioned mechanisms. Gauss fit and fast Fourier transform filtering are used for extracting the resonant wavelengths and comb spectrum, respectively. Accordingly, the temperature sensitivity of 42.18pm/°C and 2.057nm/°C are achieved by tracking the coherent decrease point. The lower sensitivity can guarantee a large dynamic range, while the higher one will contribute to the enhanced resolution. Therefore, the temperature monitoring is the combination of large dynamic range and enhanced resolution. Moreover, the size of the ultracompact sensor is only 950μm, which has a great potential for engineering applications.